Prestacao de Portugal nos Jogos Olímpicos de Pequim 2008 - Silva, A. J. (Revista Portuguesa de Ciências do Desporto, 2009)
The value at the top level sport of each nation is checked, among other events, in the largest sport event, the Olympic Games. The propose of the study is to evaluate the performance of Portugal in the Olympic Games Beijing 2008 in the sport and financial level and to compare with the performance obtained in the Olympic Games of Athena 2004. Methodology: The methodology use in the study consists in the it collects of information of several documental sources. Results: The three sport goals fastened for Portugal in the Beijing 2008 Olympic Games, they were not reached. The sport performance of Portugal translated in the number of medals and of graduate classifications he had an inferior level in Beijing 2008 than in Athena 2004. For the execution of Project Beijing 2008 was granted to Olympic Committee of Portugal a budget 12.142.876€, but the amount affected to the sport federations destined to the sport preparation and the bags, it was inferior in 154.241€, to the correspondent in Project Athena 2004. In the period of 12 years (Atlanta 1996 - Beijing 2008) the applied financial means in the olympic preparation increased in 100%, doesn`t tend the sport results accompanied with any growth.